A Numerical Study of the Behaviour of Flexible Inserts in Laminar Channel Flow - Lai, Lawrence Shien Hui (Curtin University, 2017)
The fluid-structure interactions between laminar channel-flow and pressure-loaded compliant-wall can lead to channel collapse and structural vibrations. Two-dimensional numerical simulations of fluid-conveying channels with flexible sections are conducted to investigate the steady-state and transient system behaviours. A non-dimensional scheme is developed to characterise and predict the maximum static wall deflection and the onset of self-excited oscillations. This work has applications in industrial and biomechanical engineering.